The Impact of Implementing the VAK Model in Practical Learning with Case Method to Improving Students' 21st Century Skills - Riska Dami Ristanto; Alfian Ardhiansyah; Ajeng Rahma Sudarni; Humam Nasywa Fawazi; Syarif Romadloni; Damar Hadziq Hidayatilah (Universitas Negeri Semarang, 2025)
The advancement of the Industrial Revolution 4.0 era requires university graduates to master 21st-century skills in order to actively contribute and play a role in the workforce. This necessity has become a key factor influencing graduates’ employability. However, challenges arise during the learning process, such as low student participation, limited conceptual understanding, and difficulties in developing critical thinking and problem-solving skills, particularly in practicum activities. A solution to address these issues is to implement a combination of student-centered learning models, namely the VAK (Visualization, Auditory, Kinesthetic) model, in practical learning based on the Case Method. The purpose of this study is to analyze the effect of applying the VAK model in case method–based practical learning on the improvement of students’ 21st-century skills. This research employed a Pre-Experimental Design with a One-Shot Case Study approach. The sample consisted of 94 regular class students of the PTIK Study Program at UNNES in the even semester of 2024/2025, enrolled in the Computer Networks course. The data collection instruments were based on 21st-century skill indicators, including communication, collaboration, critical thinking and problem solving, as well as creativity and innovation. Data analysis was conducted using descriptive and inferential statistics. The findings revealed that the application of the VAK model in case method–based practical learning positively influenced the enhancement of students’ 21st-century skills with a significance value of 0.001. The most significant improvements were observed in Collaboration at 87%, Critical Thinking and Problem Solving at 86.2% with a very strong category. Further research is needed to explore the ideal combination of learning models and approaches to achieve greater improvements in 21st-century skills.